2019
DOI: 10.1136/bmjopen-2018-022137
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the risk factors for catheter-associated urinary tract infections: a large cross-sectional study of six hospitals

Abstract: MotivationCatheter-associated urinary tract infections (CAUTI) are a common and serious healthcare-associated infection. Despite many efforts to reduce the occurrence of CAUTI, there remains a gap in the literature about CAUTI risk factors, especially pertaining to the effect of catheter dwell-time on CAUTI development and patient comorbidities.ObjectiveTo examine how the risk for CAUTI changes over time. Additionally, to assess whether time from catheter insertion to CAUTI event varied according to risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
93
4
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(120 citation statements)
references
References 22 publications
11
93
4
12
Order By: Relevance
“…Whereas, Letica-Kriegel AS et al found that duration of indwelling urethral catheter is a risk factor for 16.5% episodes of CAUTI. Out of these 12% of patients develop CAUTI 11. These findings are in agreement with our study.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Whereas, Letica-Kriegel AS et al found that duration of indwelling urethral catheter is a risk factor for 16.5% episodes of CAUTI. Out of these 12% of patients develop CAUTI 11. These findings are in agreement with our study.…”
supporting
confidence: 93%
“…4 3-10% of residents in United States are being managed using long term Foley catheters. 14 11 Incidence of febrile illness from a likely urinary device is 7-11/1000 catheter days, which is approximately three times more than the incidence in patients without a Foley catheter. 20 Tambyah PA et al studied that 3% of patients having catheter associated asymptomatic bacteriuria progress to bacteremia with the urinary pathogen.…”
Section: Resultsmentioning
confidence: 99%
“…There have been many kinds of urological surgery performed in the day ward mode, including lithotripsy (soft) mirror ureter, bladder calculi lithotripsy, urethra stone lithotripsy, urethra meat with resection, occult penis orthopedics, cryptorchidism by xation, stress urinary incontinence, etc. An analysis of risk factors for catheter-related urinary tract infections found that each additional day of catheter retention increased the risk of urinary tract infections [15].Since the hospital stay in the day ward mode does not exceed 24 hours, reducing the indwelling time of urinary catheters can further increase the turnover rate of patients when they are admitted to the hospital, and also greatly reduce the incidence of nosocomial infections. If postoperative infection occurs, in order to better select the appropriate antibiotic application, it is recommended that clinicians collect secretions and send them to bacterial culture as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Colonized microorganisms in the perineal skin and around the urethra can move into the urinary system through the outer surface of the urinary catheter and cause infection (14). Therefore, interventions designed to prevent the colonization of pathogens around the urinary tract can be very important in controlling CAUTIs (15). One of these interventions is the proper care of the perineal area.…”
Section: Introductionmentioning
confidence: 99%